Analysis of selected heavy metals (Fe, Pb, Cu, Cr) in surface water and sediments in Okulu River in Eleme Local Government Area of Rivers State Nigeria - Chukwudozie Colman Ifiora; G. N. Woke; Felicity Uju Onwudinjo; Chimezie Ekeke; T. M. Iringe-Koko; Paul Aforji Osaro (Humanities Horizon, 2026)
Industrial activities along riverine environments in the Niger Delta have raised serious concerns about heavy metal contamination of surface water and sediments, with potential implications for ecosystem integrity and public health. The Okulu River in Eleme Local Government Area, Rivers State, is increasingly exposed to industrial effluents, making it necessary to assess its environmental quality. The study employed an environmental analytical research design to assess heavy metal concentrations in surface water and sediments of the Okulu River in Eleme Local Government Area, Rivers State, Nigeria. Five sampling points, including four industrially impacted sites and one control, were analyzed. Surface water and sediment samples were collected, digested using mixed acids, and analyzed for Fe, Pb, Cu and Cr using Atomic Absorption Spectrophotometry. Results were statistically analyzed and compared with World Health Organization standards to evaluate contamination levels and potential environmental and health risks. The results revealed spatial variations in heavy metal concentrations in surface water and sediments of the Okulu River. Iron levels in surface water (1.401–10.46 mg/L) and sediments (1.4565–10.581 mg/L) were below the WHO limit (20 mg/L). Lead concentrations in surface water (0.029–14.91 mg/L) exceeded the WHO limit (0.01 mg/L), indicating contamination, while sediment lead levels (0.0359–36.233 mg/L) remained within the permissible limit (400 mg/L). Copper concentrations in surface water (0.002–3.814 mg/L) and sediments (0.3432–18.754 mg/L) were below WHO limits (35 mg/L). Chromium showed elevated levels in surface water (0.397–24.09 mg/L) and sediments (0.01523–15.1506 mg/L), exceeding WHO limits (0.003 mg/L). The study concludes that while some metals pose minimal risk, elevated lead and chromium levels preasent potential environmental and health concerns, underscoring the need for continuous monitoring and effective regulation of industrial discharges into the Okulu River.